Pembelajaran Bervisi Sets Model Problem Based Learning Pada Materi Daur Ulang Limbah - Rosalina Sisilia Santriana Son (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2017)
The lack of environment use as a source of learning and teaching leads to low creativity and motivation. The purpose of this study is to determine the effectiveness of the SETS Problem-Oriented Education models for the creativity and motivation of students in SMA Negeri 1 So'e. The design of this study was quasi experimental. A post-test was done to test group design. The sampling was done with targeted sample technique. The measured variable is the creativity and motivation of students in class X. The analysis was to categorize t test in the form precentage. The results showed that the visionary learning SETS PBL models affects the creativity and motivation of students in learning recycling waste material.